A case study of promoting CH4 discharge and preventing coal & gas outburst accidents by using cross-layer liquid injection technology. (February 2023) - Wen, Hu; Mi, Wan-sheng; Fan, Shi-xing; Cheng, Xiao-jiao; Li, Qi-xian; Wang, Hu; Qiu, Rui; Du, Jia-jun; Liu, Ming-yang
Abstract: To solve the problem of gas extraction in coal bodies with the outburst risk, the cross-layer drilling fluid injection technology for protecting rock pillars is adopted to promote gas extraction. We combined theoretical calculations, laboratory experiments, and field tests to analyze the degree of fissure development in different parts of the coal body. We also determined the liquid injection parameters and negative extraction pressures. The CH4 extraction effects of three stages before, during, and after liquid injection was compared. The results show that the possibility of coal outbursts in different parts is reduced by 58%∼70% by using liquid injection and pumping technology. The peak value of CH4 pure flow in the main pipe is increased by 1.5–2.8 times, and the average value is increased by 1.8–2.6 times. The peak value of gas concentration at the orifice of the extraction hole is increased by 1.6–3.5 times, and the average value is increased by 1.6–4 times. Liquid injection to promote extraction greatly improves the gas extraction efficiency in coal bodies, which is of great significance to reducing cost, shortening the construction period, and ensuring safe production, and providing a reference for similar engineering construction. Highlights: Expanded the application range of liquid injection. Outburst prevention technology of coal in rock. Comparison of flow and concentration in the whole process.